Transformational leadership and employee efficiency: Mediating role of knowledge sharing - Septa Andra Arfianto; Suhana Suhana; Nungki Pradita; Shujahat Ali; Toong Hai Sam (Universitas Ahmad Dahlan, 2025)
Transformational leadership has been widely recognized for its potential to enhance employee performance. However, the mechanisms through which this influence occurs are not fully understood.This study examines the impact of transformational leadership on employee efficiency, with knowledge sharing as a mediating variable. The research was conducted at Tumbakmas Niagasakti Company, a trading and distribution company in Indonesia. The objective is to determine the extent to which transformational leadership influences employee efficiency and whether knowledge sharing plays a significant role in this relationship. A quantitative approach using a survey questionnaire was employed to collect data from 120 employees. The collected data was analyzed using Partial Least Squares Structural Equation Modelling. The findings reveal that transformational leadership has a positive and significant impact on employee efficiency. Moreover, knowledge sharing was found to partially mediate this relationship, indicating that transformational leaders who foster a culture of knowledge sharing can enhance employee efficiency. The study contributes to the existing literature by providing empirical evidence on the mediating role of knowledge sharing in the relationship between transformational leadership and employee efficiency within an Indonesian context. The implications of these findings for organizations seeking to improve employee performance and organizational effectiveness are discussed.